Analysis of genetic improvement objectives for sheep in Cyprus - Mavrogenis A.P. (Analysis and definition of the objectives in genetic improvement programmes in sheep and goats. An economic approach to increase their profitability, 2000)
An account of the methodology employed and the procedures used for the genetic improvement of sheep in Cyprus is presented. Breeding objectives, breeding goals and selection criteria are described and justified. The breeding structure is dictated by the economic and social environment in Cyprus. Future developments in selection and evaluation procedures are presented.
Meeting of the Sub-Network on Genetic Resources of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 1999/11/18-20, Zaragoza (Spain)